Cartographie De L’erosion Qualitative Des Sols Du Bassin Versant De L’aoudour (Rif-Maroc) - Boukrim, Siham; Lahrach, Abderrahim; Midaoui, Abdelbasset; Benjelloun, Faiza; Benabdelhadi, Mohammed; Lahrach, Hamid; Chaouni, Abdel-Ali (European Scientific Journal, ESJ, 2016)
The Aoudour watershed located in the northwest of Morocco and spreads over an area of approximately 1000 km2, and occupying the northeastern part of the Ouergha basin contently experiencing the effects of severe water erosion caused by the interaction of several natural factors such as the amount and aggressiveness of rainfall, plenty of steep slopes, low vegetation density and also the dominance of friable land. The Aoudour watershed also undergoes a human action that makes it very vulnerable to environment erosion, the degradation of the vegetation cover in recent decades and also by poor farming techniques. PAP / RAC is a method of qualitative study of water erosion that can prioritize the surface of a watershed in separate units according to its vulnerability to erosion. The method consists of a descriptive and predictive mapping in relation to the identification; evaluation and integration of basic physical factors such as slope, lithology and / or soils and vegetation cover, with the aim of establish initial assumptions about the risk of erosion. The use of remote sensing and GIS tools enabled us creating and overlying of thematic maps, executing speedily the cartographic works and, processing of databases.